Activity of nintedanib in germ cell tumors. Issue 2 (February 2016) - Steinemann, Gustav; Jacobsen, Christine; Gerwing, Mirjam; Hauschild, Jessica; von Amsberg, Gunhild; Höpfner, Michael; Nitzsche, Bianca; Honecker, Friedemann
Abstract : Germ cell tumors (GCTs) are the most frequent malignancy in male patients between 15 and 45 years of age. Cisplatin-based chemotherapy shows excellent cure rates, but patients with cisplatin-resistant GCTs have a poor prognosis. Nintedanib (BIBF 1120, Vargatef) inhibits the receptor classes vascular endothelial growth factor receptor, platelet derived growth factor receptor, and fibroblast growth factor receptor, and has shown activity against many tumors, as well as in idiopathic lung fibrosis and bleomycin-induced lung injury. Here, we investigated the antineoplastic and antiangiogenic properties of nintedanib in cisplatin-resistant and cisplatin-sensitive GCT cells, both alone and in combination with classical cytotoxic agents such as cisplatin, etoposide, and bleomycin. The half-maximal inhibitory concentration (IC50 ) of nintedanib was 4.5±0.43 μmol/l, 3.1±0.45 μmol/l, and 3.6±0.33 μmol/l in cisplatin-sensitive NTERA2, 2102Ep, and NCCIT cells, whereas the IC50 doses of the cisplatin-resistant counterparts were 6.6±0.37 μmol/l (NTERA2-R), 4.5±0.83 μmol/l (2102Ep-R), and 6.1±0.41 μmol/l (NCCIT-R), respectively. Single treatment with nintedanib induced apoptosis and resulted in a sustained reduction in the capacity of colony formation in both cisplatin-sensitive and cisplatin-resistant GCT cells. Cell cycle analysis showed that nintedanib induced a strong G0/G1-phase arrest in all investigated cell lines. Combination treatment with cisplatin did not result in additive, synergistic, or antagonistic effects. The in-vivo activity was studied using the chorioallantoic membrane assay and indicated the antiangiogenic potency of nintedanib with markedly reduced microvessel density. Topical treatment of inoculated tumor plaques resulted in a significant reduction of the tumor size. This indicates that nintedanib might be a promising substance in the treatment of GCT. Abstract : Supplemental Digital Content is available in the text.